2003
DOI: 10.1046/j.1365-2117.2003.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Subsidence analyses from the Betic Cordillera, southeast Spain

Abstract: Fifty-four Mesozoic±Cenozoic stratigraphic sections from the Betic Cordillera of southeast Spain have been analysed in order to estimate the timing and amount of lithospheric stretching that occurred at the western end of the Tethyan Ocean since the Hercynian Orogeny. The standard backstripping technique has been used in order to calculate the water-loaded subsidence of basement for each section. Water-loaded subsidence curves were then inverted in order to determine the variation of lithospheric strain rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 83 publications
(138 reference statements)
1
36
0
Order By: Relevance
“…This ocean was unrelated to the oceanic systems represented by the Dinarides and Hellenides ophiolites, which developed eastward and concomitant with active subduction processes. This hypothesis is not based only on ophiolite investigations, but is supported by facies analyses and paleontological studies of coeval sedimentary sequences (Tendero et al [39]; Lemoine et al [43]; Lagabrielle et al [44]; Principi et al [77]; Perez-Lopez and Perez-Valera [94]; Critelli et al [95]; Hanne et al [96]; Martin-Rojas et al [97]; Somma et al [98]; Zaghloul et al [99]). …”
Section: Discussionmentioning
confidence: 85%
“…This ocean was unrelated to the oceanic systems represented by the Dinarides and Hellenides ophiolites, which developed eastward and concomitant with active subduction processes. This hypothesis is not based only on ophiolite investigations, but is supported by facies analyses and paleontological studies of coeval sedimentary sequences (Tendero et al [39]; Lemoine et al [43]; Lagabrielle et al [44]; Principi et al [77]; Perez-Lopez and Perez-Valera [94]; Critelli et al [95]; Hanne et al [96]; Martin-Rojas et al [97]; Somma et al [98]; Zaghloul et al [99]). …”
Section: Discussionmentioning
confidence: 85%
“…Reviews on the main aspects of the Betic margin can be found in Vera (2001) and Martín-Chivelet et al (2002) and references therein. Hanne et al (2003) have recently analysed the subsidence throughout the entire Betic cordillera. Nevertheless, certain aspects concerning the geological history of the Prebetic margin, such as the thermal evolution from Mesozoic to present, were considered for the first time only recently (Barbero et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Extension in the South Iberian margin which took place between the Lower and Middle Jurassic was clearly connected with the opening of the Central Atlantic Ocean to the west (De Jong, 1990;Srivastava et al, 1990). Therefore, the following Upper Jurassic to Santonian extension could be related to the continued opening of the Central Atlantic and synchronous development of extensional basins in the Western Tethyan area (Hanne et al, 2003;Ziegler, 1989). Examples of Mesozoic extension (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a thickened Miocene succession was deposited in the Matamoros Basin. This late extension could be related to the late Oligocene to Miocene extension that took place in the western Mediterranean region, in the Alboran Sea and in the Valencia Trough (Hanne et al, 2003;Maillard & Mauffret, 1999;Roca & Guimerà, 1992;Torné & Banda, 1992). In addition, the combined effect of the Campanian to Aquitanian contractional reactivation of pre-existing salt structures and the Miocene extensional reactivation conducted by the NE-dipping Maestre Fault, triggered passive salt extrusion of La Rosa and Jumilla diapirs ( Figure 4(b,c)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation